2019
DOI: 10.1177/1363461519861795
|View full text |Cite
|
Sign up to set email alerts
|

Cultural concepts of distress and psychiatric disorders: Understanding symptom experience and expression in context

Abstract: The term ''cultural concepts of distress'' (CCD) was introduced in DSM-5 to better characterize the broad set of constructs identified in clinical and ethnographic research on cultural variations in distress. 1 Much work in medical anthropology on cultural variations in distress has been framed in terms of ''idioms of distress'' (Nichter, 1981, 2010) and this is the term used by most of the articles in this special issue to cover a range of symptoms, syndromes, and modes of expression. In the DSM-5, however, '… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(81 citation statements)
references
References 45 publications
1
72
0
Order By: Relevance
“…In the context of extreme oppression, MPI symptoms may function as a psychological defense or social expression of distress that is comprehensible in terms of local cultural models of affliction (101,102). MPI symptoms may operate as local cultural idioms of distress, modes of communication that serve the afflicted individual's ongoing efforts to adapt to and survive in challenging social circumstances (103)(104)(105)(106). Ethnographic studies have suggested, for example, that spirit possession may provide women or marginalized subgroups with the means to express distress in contexts where more direct expression is impossible or may have adverse effects (107,108).…”
Section: Resultsmentioning
confidence: 99%
“…In the context of extreme oppression, MPI symptoms may function as a psychological defense or social expression of distress that is comprehensible in terms of local cultural models of affliction (101,102). MPI symptoms may operate as local cultural idioms of distress, modes of communication that serve the afflicted individual's ongoing efforts to adapt to and survive in challenging social circumstances (103)(104)(105)(106). Ethnographic studies have suggested, for example, that spirit possession may provide women or marginalized subgroups with the means to express distress in contexts where more direct expression is impossible or may have adverse effects (107,108).…”
Section: Resultsmentioning
confidence: 99%
“…In this context, one has to consider that beliefs surrounding causes of illness, evaluation of treatment, and stigmatization are largely socially and culturally constructed (Kleinman, 1980; Lewis-Fernández & Kirmayer, 2019; Link & Phelan, 2001). In Syria, suffering is commonly conceptualized as a part of life that one must handle, often resulting in very indirect expressions of mental health problems (see Hassan et al, 2015, for a provision of specific idioms that Syrians use to express distress).…”
mentioning
confidence: 99%
“…Scholars like Devon Hinton (Hinton, Pich, Marques, Nickerson & Pollack, 2010;Hinton, Reis & de Jong, 2015) have proposed extensive research agendas to incorporate and test the use of idioms of distress in interventions. And in the most recent version of the DSM (5th edition, 2013), the term ''cultural concepts of distress'' has replaced the outdated terminology of culture-bound syndromes (Lewis-Ferna´ndez & Kirmayer, 2019). This change was intended to signal a broader, more inclusive understanding of culturally specific distress as something that changes over time and does not represent place-specific ''exotica.''…”
Section: Introductionmentioning
confidence: 99%